2018
DOI: 10.1111/epi.14515
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of status epilepticus: A critical assessment

Abstract: SummaryWe reviewed 37 studies reporting long‐term outcomes after a status epilepticus (SE) episode in pediatric and adult populations. Study design, length of follow‐up, outcome measures, domains investigated (mortality, SE recurrence, subsequent epilepsy, cognitive outcome, functional outcome, or quality of life), and predictors of long‐term outcomes are summarized. Despite heterogeneity in the design of prior studies, overall risk of poor long‐term outcome after SE is high in both children and adults. Etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 94 publications
9
89
3
7
Order By: Relevance
“…Our study identified a significant increase in short‐term mortality with increasing SE duration, a finding in line with those of prior studies . A recent review of 37 studies regarding long‐term outcome of patients surviving SE revealed that the long‐term effect of SE duration on outcome is often difficult to distinguish from the underlying cause of SE . In our cohort, the RR for death of 1.06 with every additional day in SE equals an increase in risk of death of 6% per 24 hours.…”
Section: Discussionsupporting
confidence: 91%
“…Our study identified a significant increase in short‐term mortality with increasing SE duration, a finding in line with those of prior studies . A recent review of 37 studies regarding long‐term outcome of patients surviving SE revealed that the long‐term effect of SE duration on outcome is often difficult to distinguish from the underlying cause of SE . In our cohort, the RR for death of 1.06 with every additional day in SE equals an increase in risk of death of 6% per 24 hours.…”
Section: Discussionsupporting
confidence: 91%
“…20 Long-term outcome after SE is still challenging, and studies in this context are difficult to compare because of the heterogeneity of their design. 21 Our study provides a first and promising result regarding the predictive value of illness severity scoring systems in ICUs in this context. However, mortality after 30 days could not be assessed in this observational cohort.…”
Section: Discussionmentioning
confidence: 79%
“…Data regarding the prediction of long‐term outcome and quality of life after SE are scarce, but complete long‐term recovery from SE is possible . Long‐term outcome after SE is still challenging, and studies in this context are difficult to compare because of the heterogeneity of their design . Our study provides a first and promising result regarding the predictive value of illness severity scoring systems in ICUs in this context.…”
Section: Discussionmentioning
confidence: 84%
“…Status epilepticus (SE), as an extreme form of epileptic seizures, can prolong for a sufficient length of time and produce irreversible insult to the brain (Trinka et al, 2015). Long-term sequelae of SE could ultimately devastate patients' quality of life and impose an overwhelming social and economic burden (Sculier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%